ЭСХАТОЛОГИЧЕСКИЕ ОБРАЗЫ «СЛОВА» ПАЛЛАДИЯ МНИХА (К ВОПРОСУ О КРУГЕ ЧТЕНИЯ ПЕЧОРСКИХ КРЕСТЬЯН-СТАРООБРЯДЦЕВ) - Волкова, Татьяна (Acta Neophilologica, 2018)
This article, based on the existing few studies, provides basic information on the translated eschatological work – “The Word (Sermon) of Palladium Mnich”, widely spread in Russia, especially among the Old Believer peasants. Such features as the time of creation, the alleged author, and the influence on subsequent eschatological works are discussed. The author analyzes the composition of “Sermon of Palladium Mnich”, characterizes the eschatological images in the “Word”, gives information about the Pechora lists of the “Sermon” and describes the features of their text.